The correlation functions and estimation of global solar radiation studies using sunshine based model for Kano, Nigeria - Sani, G. D/iya; Mohd Ekhwan, Toriman; Mohd Barzani, Gazim; Usman, M. Gana; Musa, G. Abdullahi (2015)
The use of empirical models for the comparative study of the correlation functions for the estimation of global solar radiation in Kano, Nigeria has been carried out. The models used are based on relative sunshine duration alongside the measured global solar radiation data, such as: the linear model = (a +b), the quadratic model = [ a + b +c() ]and the cubic model = [ a + b() + c() + d() ]. The models constants a ,b ,c and d will be used in calculating the estimated value of global solar radiation and also the agreement between the measured and estimated values. The statistical parameters used for the comparative techniques are: the mean bias error (mbe), mean percentage error (mpe) and the root mean square error (rmse), which will be use to determine the efficiency of the estimation. Subsequently, the result obtained for the models constants a and b are 0.045 and 0.051 respectively and the estimated values of global solar radiation are 21.4, 22.6, 22.2, 22.2 and 21.8 for the year 2006, 2007, 2008, 2009 and 2010 respectively. Similarly, the correlation functions obtained for all the three models are above 0.8, which shows that the estimation is good. Consequently, the developed model will be use confidently for Kano and nearby locations which has similar climatic conditions.